Rapid prey manipulation and bite location preferences in three species of wandering spiders (2024)
Predator-prey interactions are the interspecific relationships of greatest interest in ecology. Spiders are among the most diverse and ubiquitous terrestrial predators on the planet. Their large dietary breadth is often linked with the development of specific predatory behaviors and morphological adaptations. However, studies on the predatory behavior of spiders have mostly focused on specialist species, leaving behind the ethological variability occurring in generalist species that allow them to respond to the different prey types. For three species of generalist wandering spiders, we searched images of predation events on the Internet to determine the most common prey. Subsequently, the focal predator species were then used in behavioral experiments. Using high-speed videos, handling patterns for different prey types (spider and cricket) were analyzed. Our results show a notable difference in handling patterns between prey types. We found that the spider prey was often rotated around the axis allowing the predator to bite in the ventral region of the prey and thus avoid a counterattack. Contrary, crickets were arbitrarily rotated. Our work may be an indication that these three species of generalist spiders have a preference for manipulating prey differently with a preference to rotate spiders, allowing them to exploit prey with various defensive mechanisms.